DELIVERY INSTRUMENTAL IN MODERN OBSTETRICS EXPERIENCE AND SYSTEMATIC REVIEW - Sotero, Gonzalo (2015)
OBJETIVE: To analyze the casuistry of CHPR of the last five years, to analyze the place of instrumental delivery, its results, and since the reintroduction of the vacuum extractor, a systematic review comparing the qualities between both methods. METHODS: A systematic review on the use of instrumental delivery. RESULTS: The number of instrumental deliveries in the Hospital is similar to other reference centers and is within the accepted; perinatal maternal outcomes are similar to those of normal deliveries. CONCLUSION: The choice of vacuum vs. forceps, the decision lies primarily in training technical.